Identifying areas where biodiversity is at risk from potential cocoa expansion in the Congo Basin - Kamath, Vignesh; Sassen, Marieke; Arnell, Andy; van Soesbergen, Arnout; Bunn, Christian (Elsevier, 2024)
The growing global demand for cocoa is leading to large-scale land-use changes and habitat loss in biodiversity rich areas such as the tropical lowland forests of Africa. Low productivity and climate change are projected to affect cocoa production in major parts of West Africa, where most of the world’s cocoa is produced. Such effects are expected to drive expansion into Central Africa where governments are looking towards commodity crop production, including cocoa, to support economic development objectives. For example, Cameroon is the fifth largest cocoa producer in the world and aims to triple its cocoa production volume by 2030. A tripling in yields is unlikely, especially within that timeframe, meaning this will only be possible through expansion. In conflict with this trajectory is new legislation in the UK and the EU, banning the import of commodities linked to deforestation. Cocoa is the fastest expanding export crop in Sub-Saharan Africa, but little is known about potential expansion areas in the Congo Basin and how this will impact biodiversity. In this study, we attempt to address this gap by answering two questions: (i) Where are available suitable areas to grow cocoa in the Congo Basin? (ii) Where are the likely impacts of cocoa expansion on biodiversity? We followed a spatial exclusionary approach to identify available areas for cocoa cultivation within areas with moderate to high climatic suitability for cocoa. This was achieved by identifying and excluding land-use and land cover types that are unsuitable for cocoa expansion under different assumptions. We then identified areas of high risk within the available area for cocoa as those with high cocoa suitability and high biodiversity significance (i.e., rarity-weighted species richness) and high accessibility. The study highlights the Congo Basin's central belt as an area where biodiversity would be put at high risk from cocoa expansion. Even with an effective no deforestation policy, biodiversity loss remains a concern in agricultural areas like western Cameroon and the northeastern and eastern edges of the Democratic Republic of the Congo. This research provides valuable insights that can be used to guide the development of strategies that mitigate the adverse effects of cocoa expansion on biodiversity.